Green Marketing –Practices and Challenges in the Indian Context - Mani, Ambica Prakash; Bhandari, Samridhi (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*288.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932403);" role="presentation">This research is an attempt to explain the concept of green marketing and practices that are adopted by some <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*301.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941916);" role="presentation">renowned companies in India. Green marketing is the practice of producing, using, consuming, recycling and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*314.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978014);" role="presentation">disposing products that are less burdens<span dir="ltr" style="left: calc(var(–scale-factor)*247.13px); top: calc(var(–scale-factor)*314.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00845);" role="presentation">ome for the environment. The concept gained popularity when <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*327.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906775);" role="presentation">environmental concerns stared occupying the centre stage and ecological concerns were riding everyone’s mind. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*340.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919249);" role="presentation">During this time a new segment of consumers appeared on the timeline, these consumers <span dir="ltr" style="left: calc(var(–scale-factor)*439.63px); top: calc(var(–scale-factor)*340.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895762);" role="presentation">are referred as green <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*354.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891226);" role="presentation">consumers, particular due to their concern for environmental issues. These consumers displayed green purchasing <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*367.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891036);" role="presentation">by adopting products that are non toxic and have less ecological concerns. The concerns of these consumers were <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*380.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915163);" role="presentation">reciprocat<span dir="ltr" style="left: calc(var(–scale-factor)*112.10px); top: calc(var(–scale-factor)*380.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903581);" role="presentation">ed by a number of leading companies that are adopting practices for protecting and preserving the flora <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*393.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901927);" role="presentation">and fauna, there by bearing the flag for sustainable development.